From Bookkeeping to Brainpower: A Systematic Literature Review on Artificial Intelligence in Accounting Organizations - Wafiq Azizah Reski Amaliah; Mubdi Dzuwhandy; Grace Theresia Pontoh; Aini Indrijawati (IECON: International Economics and Business Conference, 2025)
The ongoing shift toward digitalization has paved the way for AI to become embedded in the evolution of modern accounting functions. AI is no longer merely a technical tool, but has become an institutional agent that transforms work structures, professional roles, and decision- making processes within accounting organizations. This study aims to systematically examine the impact of AI on operational efficiency, the shifting roles of accountants, accompanying ethical challenges, and the emergence of new strategic opportunities in the context of accounting organizations. Using the PRISMA-based Systematic Literature Review (SLR) approach, this study analyzes 44 international scientific articles published between 2015 and 2025. The findings are categorized into four main themes: (1) AI and the redefinition of efficiency; (2) the transformation of the accountant's role: from compliance to cognition; (3) ethical dilemmas and strategic risks; and (4) new opportunities and value creation arising from AI adoption. This study also identifies limitations in the literature, including the lack of longitudinal studies, dominance of developed country perspectives, and limited interdisciplinary exploration. This study contributes to expanding the understanding that AI is not merely an efficiency instrument, but a social force that reconstructs the accounting profession and opens up a new landscape of value creation. Practical implications include the need for accountant retraining, strengthening ethical governance, and proactive utilization of AI for financial service innovation. Long-term research directions include integrating AI with complementary technologies like Blockchain, IoT, and ESG principles to design accounting systems that are intelligent, flexible, and environmentally responsible.